DEVELOPMENT AND VALIDATION OF ULTRAVIOLET SPECTROPHOTOMETRIC METHOD FOR QUANTITATIVE ESTIMATION OF FAMOTIDINE IN BULK AND TABLET DOSAGE FORM - Kumar, Ritesh; Chandra, Amrish; Gautam, Pawan Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objectives: The purpose of the study is to develop a simple, precise, economical, accurate, reproducible, and sensitive method for the estimation of famotidine (FAM) in bulk and its pharmaceutical dosage forms by ultraviolet (UV) absorption spectrophotometry. Methods: The method uses 0.1 N HCl, pH 1.20 as a solvent for the quantitative estimation of FAM in bulk and its tablets dosage form by UV absorption spectrophotometry. Results: FAM exhibited absorbance maxima at 266 nm in 0.1 N HCl, pH 1.20 solvent. The developed method was validated as per the ICH analytical method validation guidelines. Beer's law was obeyed in range of 0-30 Î¼g/ml with r2=0.9998. The limit of detection and limit of quantification values of FAM were found to be 0.152 and 0.461 Î¼g/ml, respectively. The mean percentage recovery for developed method was found to be in the range of 99.35-99.48%, respectively, for the marketed dosage forms. The developed method was also found to be robust and ensures bench-top stability. Conclusion: The developed method was found to be suitable for the routine quantitative analysis of FAM in bulk and pharmaceutical dosage form. It was also concluded that developed UV spectrophotometry method was accurate, precise, linear, reproducible, robust, and sensitive.